NSW Aboriginal Justice Advisory Council - NSW Department of Education Aboriginal Education and Training Policy - Aboriginal Justice Advisory Council (N.S.W.); Joseph, Samantha ([Sydney, N.S.W.] : Aboriginal Justice Advisory Council)
Contains AJAC's response to the NSW Department of Education Aboriginal Education and Training Policy.
Listed on website under Submissions as: AJAC's response to the NSW Department of Education Aboriginal Education and Training Policy.
Signed by Samantha Joseph.
Title from title screen (viewed on 2 December 2008).
Available via World Wide Web. On 2/12/08 available from website of NSW Aboriginal Justice Advisory Council at: http://www.lawlink.nsw.gov.au/lawlink/ajac/ll_ajac.nsf/pages/ajac_submissions
System requirements: Adobe Acrobat Reader to view/print PDF files
Selected for archiving
Keywords: New South Wales. -- Department of Education and Training; Aboriginal Australians -- Education -- New South Wales; Aboriginal Australians -- Government policy -- New South Wales; Education and state -- New South Wales